Efektivitas Pendekatan Segitiga Restitusi dalam Pendidikan Agama Islam untuk Meningkatkan Disiplin Siswa Sekolah Menengah Kejuruan di Boyolali (Studi Kasus SMK N 1 Sawit dan SMK Muhammadiyah 1 Boyolali) - Widiyarto, Angga; Chusniatun, Chusniatun; Ali, Mohamad (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
This research aims to: (1) Explain the application of the Restitution Triangle in Islamic religious education to improve student discipline at SMKN 1 Sawit Boyolali and SMK Muhammadiyah 1 Boyolali (2) Analyze the similarities and differences in the application of the Restitution Triangle in Islamic religious education to improve student discipline at SMKN 1 Sawit Boyolali and SMK Muhammadiyah 1 Boyolali (3) Explain the impact/results of the application of the Restitution Triangle in Islamic religious education for students at SMKN 1 Sawit Boyolali and SMK Muhammadiyah 1 Boyolali This research uses a qualitative approach with the type of case study conducted in two locations, namely SMK Negeri 1 Sawit and SMK Muhammadiyah 1 Boyolali. The research subjects included PAI teachers, students, and school principals. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation studies. The results showed that PAI teachers applied the restitution triangle as a solution to handling discipline problems, and there were differences where SMK N 1 Sawit wanted to switch completely from the punishment method, but at SMK Muhammadiyah 1 Boyolali, collaboration between the punishment and the restitution triangle. The application of the restitution triangle is proven to have a positive impact on improving student discipline, both in terms of attendance, compliance with school rules, and responsibility in carrying out learning tasks. This study concludes that the restitution triangle is an effective and relevant approach in strengthening discipline and character education through PAI learning in vocational schools.   Keywords: Restitution Triangle, Islamic Religious Education, Discipline, Vocational High Schools